Three Individuals with PURA Syndrome in a Cohort of Patients with Neuromuscular Disease - Mroczek, Magdalena; Zafeiriou, Dimitrios; Gurgel-Gianetti, Juliana; Vilela Morais de Azevedo, Beatriz; Roos, Andreas; Bartels, Enrika; Kohlschmidt, Nicolai; Phadke, Rahul; Feng, Lucy; Duff, Jennifer; Töpf, Ana; Straub, Volker (Neuropediatrics, 2020)
Pur-α protein (PURA) syndrome manifests in early childhood with core features such as neurodevelopmental and speech delay, feeding difficulties, epilepsy, and hypotonia at birth. We identified three cases with PURA syndrome in a cohort of patients with unexplained muscular weakness, presenting with a predominantly neuromuscular and ataxic phenotype. We further characterize the clinical presentation of PURA syndrome including myopathic facies and muscular weakness as the main clinical symptoms in combination with elevated serum creatine kinase levels. Furthermore, we report two novel variants located in the conservative domains PUR-I and PUR-II. For the first time, we present the muscle biopsies of PURA syndrome patients, showing myopathic changes, fiber size variability, and fast fiber atrophy as the key features. PURA syndrome should be taken into consideration as a differential diagnosis in pediatric patients with unexplained muscle weakness.
Keywords: PURA syndrome; fast fiber atrophy; neurodevelopmental delay